Contemporary electric circuits : insights and analysis - Strangeway, Robert A., ....-; Gassert, John D., ....-; Petersen, Owe G., ....- (Upper Saddle River : Pearson, 2006)
For combined DC/AC Circuit Analysis courses and separate DC and AC Circuit Analysis courses in Engineering Technology and Technology programs. This succinct, but thorough treatment of DC and AC circuits analysis effectively communicates the concepts and techniques of circuit analysis with a focused practical style that keeps students motivated. The text starts at a level that the majority of students can grasp and continues with clear, focused explanations that advance students to the desired level proficiency.
Keywords: Vermogenselektronica